PMSM Model for Sensorless Control Considering Saturation Induced Secondary Saliencies - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (2013)
Saliencies in electric machines are caused by the machine geometry and saturation. PMSM typically do not just show a single sinusoidal saliency, which is the main saliency utilized for position tracking. Secondary saliencies are a major source of deterioration for sensorless control, whereby saturation is reported to be the main problem. Cross-saturation, caused by a movement of the main flux away from the d-axis, results in steady-state position estimation errors. Moreover saturation can result in 6n-harmonic components in the inductances in field oriented coordinates. This effect causes position dependent estimation errors. Both effects need to be compensated for, if significant. For model based compensation a machine model with time-variant parameters is needed to cope with nonlinear material characteristics. A general machine model in field oriented coordinates considering multiple saliencies is derived and a method for systematic determination of the position dependent inductances is proposed. The machine model is verified by test bench measurement results.